Intra-Osseous Arthrodesis Techniques in the Foot and Ankle: Does it Really Hurt Less?. Issue 1 (19th August 2016) - Haydel, Christopher; Eremus, Joseph; Lachman, James R.
Category: Ankle Arthritis Introduction/Purpose: Arthrodesis is considered the standard operative treatment for end-stage arthritis in the foot and ankle. The long-term effects of implant choices for fusions are largely unexplored in the literature. Many companies advertise implants as being "lower profile" and "less painful." The purpose of this study was to perform a clinical and radiographic review to determine outcomes, specifically rates of symptomatic hardware, using four major arthrodesis techniques in joints in the foot and ankle. Methods: A retrospective study was conducted including one-hundred and twenty-three patients (a total of 197 joints) who underwent arthrodesis of the ankle, or joints in the midfoot or hindfoot. A total of 197 joints underwent arthrodesis in this patient group. Four groups were created based on fixation methods; standard screw fixation, plate and screw fixation, screw-in- post fixation(so-called "intra-osseous" fixation), and a group using a combination of fixation methods. Through chart review and radiographic analysis, outcomes including fusion rate, pain at specific follow-up intervals(6-weeks, 3-months, 6-months, and 1-year), and symptomatic hardware requiring hardware removal were compared across groups. Results: No differences were found in fusion rates between the four groups. Non-union rates, hardware loosening, infection, and wound breakdown rates were all comparable across the cohort. Rates of reported pain at 6-weeks and 3-months were similar for all groups but the "plate and screw fixation" group reported significantly more pain at 6 months(p=0.035) and 1 year(p=0.022) than the other three groups and, subsequently, rates of symptomatic hardware requiring removal were significantly higher in this group as well. The patient population had higher rates of diabetes mellitus, human-immunodeficiency virus (HIV) and hepatitis C virus (HCV) than reported in recent studies of comparable design. Conclusion: In this high risk patient population, implant choice in arthrodesis of the midfoot, hidfoot or ankle has a significant effect on patient-reported pain during follow-up. In this cohort, the group fused with intra-osseous fixation methods did not demonstrate superiority with regards to rates of patient-reported post-operative pain related to hardware. Clinicians should expect significantly increased rates of symptomatic hardware when using plate fixation in fusions of the ankle, midfoot and hindfoot.